2014
DOI: 10.1155/2014/806586
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoacrylate Injection Compared with Band Ligation for Acute Gastric Variceal Hemorrhage: A Meta-Analysis of Randomized Controlled Trials and Observational Studies

Abstract: Background. Cyanoacrylate injection (GVO) and band ligation (GVL) are effective treatments for gastric variceal hemorrhage. However, data on the optimal treatment are still controversial. Methods. For our overall analysis, relevant studies were identified from several databases. For each outcome, data were pooled using a fixed-effect or random-effects model according to the result of a heterogeneity test. Results. Seven studies were included. Compared with GVL, GVO was associated with increased likelihood of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…42-44 In a recent meta-analysis involving 648 patients with bleeding gastric varices (all types), pooled analysis suggested better efficacy of EVO in achieving primary hemostasis, and lower rebleeding rates (OR 2.32; 95% CI 1.19-4.51). 45 There was no difference between EVO and EVBL in terms of mortality, complications and number of treatment sessions required for complete variceal eradication. There were significant heterogeneity among the studies in terms of techniques used, type and dose of cyanoacrylate, number of injections, however.…”
Section: Endoscopic Management Of Gastric Variceal Hemorrhagementioning
confidence: 83%
“…42-44 In a recent meta-analysis involving 648 patients with bleeding gastric varices (all types), pooled analysis suggested better efficacy of EVO in achieving primary hemostasis, and lower rebleeding rates (OR 2.32; 95% CI 1.19-4.51). 45 There was no difference between EVO and EVBL in terms of mortality, complications and number of treatment sessions required for complete variceal eradication. There were significant heterogeneity among the studies in terms of techniques used, type and dose of cyanoacrylate, number of injections, however.…”
Section: Endoscopic Management Of Gastric Variceal Hemorrhagementioning
confidence: 83%
“…Several systematic reviews/meta-analyses have evaluated the efficacy of cyanoacrylate injection for the treatment of GVH [105][106][107][108][109] also significantly better in preventing the recurrence of gastric varices (36.0 % vs. 66.0 %; P = 0.002). There was no difference in AEs or mortality between the two groups.…”
Section: Initial Managementmentioning
confidence: 99%
“…Several systematic reviews/meta-analyses have evaluated the efficacy of cyanoacrylate injection for the treatment of GVH 105 106 107 108 109 . Qiao et al reported on three RCTs, which included 194 patients with active gastric variceal bleeding, comparing endoscopic cyanoacrylate injection versus EBL 106 .…”
Section: Endoscopic Managementmentioning
confidence: 99%
“…29 It has proven to be more effective and safer than band ligation and sclerotherapy in this subset of patients and has been considered as standard therapy in Europe, the Middle East, and Asia for more than 25 years. 30 In our daily practice, we use always a mixture of N-butyl-2-cyanoacrylate and lipiodol for bleeding gastric varices using a dedicated 21-gauge needle with the purpose of obliterating the bleeding gastric varices and those at risk to bleed (Supplementary Video 2). 31 Novel Endoscopic Modalities for Variceal Bleeding…”
Section: Management Of the Acute Variceal Bleeding Episodementioning
confidence: 99%